A hackathon as a tool to enhance research and practice on electronic health record systems’ interoperability for chronic disease management and prevention - Rigas, Emmanouil S.; Kostomanolakis, Stavros; Kyriakoulakos, Nikolaos; Kounalakis, Dimitrios; Petrakis, Ioannis; Berler, Alexander; Boumpaki, Asimina; Karanikas, Haralampos; Kelepouris, Athanasios; Bamidis, Panagiotis D.; Katehakis, Dimitrios G. (Frontiers in Digital Health, 2023)
The development of a standardized technical framework for exchanging electronic health records is widely recognized as a challenging endeavor that necessitates appropriate technological, semantic, organizational, and legal interventions to support the continuity of health and care. In this context, this study delineates a pan-European hackathon aimed at evaluating the efforts undertaken by member states of the European Union to develop a European electronic health record exchange format. This format is intended to facilitate secure cross-border healthcare and optimize service delivery to citizens, paving the way towards a unified European health data space.The hackathon was conducted within the scope of the X-eHealth project. Interested parties were initially presented with a representative clinical scenario and a set of specifications pertaining to the European electronic health record exchange format, encompassing Laboratory Results Reports, Medical Imaging and Reports, and Hospital Discharge Reports. Additionally, five onboarding webinars and two professional training events were organized to support the participating entities. To ensure a minimum acceptable quality threshold, a set of inclusion criteria for participants was outlined for the interested teams.Results: Eight teams participated in the hackathon, showcasing state-of-the-art applications.These teams utilized technologies such as Health Level Seven -Fast Healthcare Interoperability Resources (HL7 FHIR) and Clinical Document Architecture (CDA), alongside pertinent IHE integration profiles. They demonstrated a range of complementary uses and practices, contributing substantial inputs towards the development of future-proof electronic health record management systems.The execution of the Hackathon demonstrated the efficacy of such approaches in uniting teams from diverse backgrounds to develop state-of-the-art applications. The outcomes produced by the event serve as proof-of-concept demonstrators for managing and preventing chronic diseases, delivering value to citizens, companies, and the research community.